Exosomes as novel biomarkers in sepsis and sepsis related organ failure - Yixuan Yuan; Yujie Xiao; Jiazhen Zhao; Lixia Zhang; Mengyang Li; Liang Luo; Yanhui Jia; Kejia Wang; Yuxi Chen; Peng Wang; Yuhang Wang; Jingtao Wei; et al. (Journal of Translational Medicine)
Abstract Sepsis, a severe and life-threatening condition arising from a dysfunctional host response to infection, presents considerable challenges to the health care system and is characterized by high mortality rates and substantial economic costs. Exosomes have garnered attention as potential diagnostic markers because of their capacity to mirror the pathophysiological milieu of sepsis. This discourse reviews the progression of sepsis classification from Sepsis 1.0 to Sepsis 3.0, highlighting the imperative for sensitive and specific biomarkers to facilitate timely diagnosis and optimize patient outcomes. Existing biomarkers, such as procalcitonin (PCT) and C-reactive protein (CRP), exhibit certain limitations, thereby prompting the quest for more dependable diagnostic indicators. Exosomal cargoes, which encompass proteins and miRNAs, present a trove of biomarker candidates, attributable to their stability, pervasive presence, and indicative nature of the disease status. The potential of exosomal biomarkers in the identification of sepsis-induced organ damage, including cardiomyopathy, acute kidney injury, and acute lung injury, is emphasized, as they provide real-time insights into cardiac and renal impairments. Despite promising prospects, hurdles persist in the standardization of exosome extraction and the need for extensive clinical trials to validate their efficacy. The combination of biomarker development and sophisticated exosome detection techniques represents a pioneering strategy in the realm of sepsis diagnosis and management, underscoring the significance of further research and clinical validation. Graphical Abstract